New insights into an old disease: advanced imaging in the diagnosis and management of gout. Issue 1048 (30th October 2012) - McQueen, Fiona Marion; Reeves, Quentin; Dalbeth, Nicola
Abstract : Advanced imaging modalities including MRI, ultrasound (US), CT and dual energy CT have important applications in gout. While conventional radiography (X-ray) remains the most widely used form of imaging in the clinical setting and is helpful in revealing erosions in chronic gout, these new imaging tools can reveal joint damage and tophi at a much earlier stage. As all are multiplanar techniques, they can define the position and dimensions of tophi, with startling clarity, as well as the size and extent of bone erosions. US and MRI also reveal the severity of inflammation within and adjacent to the joint and can capture information about the composite, vascular nature of many tophaceous deposits. These features can be used as imaging outcome measures, to monitor responses to anti-inflammatory and urate lowering therapies. The new possibility that gout could be diagnosed using imaging, without aspirating the joint, is on the horizon. This review discusses the clinical and research applications of advanced imaging in gout with particular focus on diagnosis and monitoring of joint inflammation and damage.